THE ROLE OF TAXES IN THE FORMATION OF LOCAL BUDGET REVENUES - Kimsanbaeva Maftuna Bakhodirovna (Modern American Journals, 2025)
Practical proposals and recommendations were proposed on the importance of taxes in the formation of local budget revenues and on increasing the efficiency of local budget revenues.
Keywords: Budget capacity, inter-budgetary transfers, local budget, local budget revenues, local budget expenditures, local taxes, tax revenues, financial independence, local government.